METAPHORS ON JOHN LEGEND’S SONG "ALL OF ME": COGNITIVE SEMANTICS - Tumanggor, Orli Binta; Siahaan, Desta Gloria (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2023)
Metaphor is widely used in everyday life. In the cognitive-semantic approach, the meaning of language is associated with mental issues, and metaphor is considered an important matter in categorizing the world and human thinking processes as a tool to conceptualize an abstract experience domain into a concrete one in cognitive semantics. Metaphor is not only used in daily conversation but also in song. This study was aimed at investigating the varied metaphors: orientational metaphor, ontological metaphor, and structural metaphor used on the song "All of Me" by John Legend. It was found that there were 3 orientational metaphors, 8 ontological metaphors, 5 structural metaphors, in which one clause deals with both orientational and structural metaphors. The common use of metaphors was needed to be understood in English communication.